البانتشاسيلا بين القبول والرد - Akhmadul Faruq (Dirosat : Journal of Islamic Studies, 2021)
Abstrak: Indonesia is a republic nation that Muslims as majority of nitizen have played considerable role even since the struggle for Indonesian independence. Nonetheless, the country indeed does not necessarily adhere to Islamic system, rather instead to the so-called ‘Pancasila’ (Five Principles), e.g. belief in the One and Only God, just and civilized humanity, unity of Indonesia and democratic rule that is guided by the strength of wisdom resulting from deliberation so as to realize social justice for all the people of Indonesia. In the fact, Pancasila itself actually has raised a hotly-debated discussion in both politics and religion till Indonesian today, particularly in the matter of Islamic values enactment. Because of that, the present study aims to find the argumentations from both of sides and the intersection of the dispute by employing the inductive and analytic method with involves gathering and analyzing material relevant to the research. The study eventually concluded that most Pancasila’s values both its theory and interpretation, according to the People’s Consultative Assembly, are not in accordance with that of Islamic values. The democracy that lies under Pancasila in fact does not benefit to the people, instead it merely acts as a slogan, formality, meaninglessness, and purely theoritcal. Keywords: Pancasila, Islamic values, hotly-debated discussion. إن إندونيسيا دولة كان المسلمون فيها يلعبون دورا مهمّا في استقلالية جمهورية إندونيسيا من قبضة الاستعمار الأجنبي، كما أنهم يشكلّون الغالبية العظمى من الشعب الإندونيسي. وعلى الرغم من ذلك إلا أنها لا تحكم بالشريعة الإسلامية بشكل كامل شامل، بل كانت الدولة تقوم على أساس البانتشاسيلا (المبادئ الخمسة)، وهي: الربانية المتفردة، والإنسانية العادلة المهذبة والمتحضرة، والوحدة الإندونيسية، والشعبية الموجهة بالحكمة والحصافة في الشورى النيابية، والعدالة الاجتماعية لكل المواطنين الإندونيسيين، فهي أساس فلسفي ومصدر أساسي للقانون الوطني والنظام القانوني لجمهورية إندونيسيا. لذلك،.  فليست جمهورية إندونيسيا بالبلد الثيوقراطي ولا العلماني ولا الشيوعي بل هي دولة البانتشاسيلا.